Polyaniline / phytic acid electrode covered with hydrogel, preparation method of polyaniline / phytic acid electrode and application of polyaniline / phytic acid electrode in pH sensor
By covering the polyvinyl alcohol/sodium alginate hydrogel on the surface of the polyaniline/phytate electrode, the limitations of existing electrode materials for liquid pH detection are solved, and high sensitivity detection of pH changes of volatile gases and non-destructive monitoring of fish freshness are achieved.
Patent Information
- Application Number
- CN202510085498.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-15
AI Technical Summary
The existing electrode materials prepared with polyaniline as the precursor can only be used for pH-sensitive reactions of liquid substances and have low sensitivity.
The polyaniline/phytic acid electrode covering the hydrogel is used to cover the polyvinyl alcohol/sodium alginate hydrogel on the electrode surface, breaking through the limitation that traditional electrodes can only detect liquids, and achieving electrochemical signal reflection on the pH changes of volatile gases.
It improves the sensitivity to pH, can efficiently monitor the freshness of fish, and keeps the electrode functioning well through the water retention of the hydrogel, achieving non-destructive monitoring.
Smart Images

Figure CN119827599A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of food technology, in particular to a polyaniline / phytic acid electrode covered with a hydrogel and a preparation method thereof and application in a pH sensor. Background Art
[0002] pH value is of great significance in the field of food testing, as it can reflect the degree of food deterioration. At present, the methods for detecting the pH value of food include pH test paper method, pH meter method, and indicator method. However, the pH test paper method cannot measure the exact value of the sample, and the subjective judgment of color by the naked eye is prone to errors; the pH meter is large in size and not easy to be used in food packaging, and the instrument needs regular maintenance; the indicator method can only know a certain range of pH values, has poor stability, color interference, and is prone to errors. Polyaniline (PANI) is a polymer compound with unique electrical and optical properties and broad application prospects. As an electrode material, polyaniline is not only low in cost, stable, and easy to process, but also has the advantages of good conductivity and environmental friendliness. In addition, polyaniline exhibits sensitive characteristics to pH. The amine group and benzene ring in the molecular structure of polyaniline undergo protonation and deprotonation reactions under different pH conditions, resulting in changes in the charge state and conformation of the polymer chain. This process affects the charge transfer capacity in the polymer chain. This leads to the phenomenon that the conductivity of polyaniline changes with the change of pH value. In the prior art, electrode materials prepared using polyaniline as a precursor can detect pH, but such materials are currently mainly used for pH-sensitive reactions of liquid substances, and their sensitivity needs to be improved. Summary of the invention
[0003] [Technical issues]
[0004] The present invention aims to solve the problem that the existing electrode material prepared by using polyaniline as a precursor can only be used for pH sensitive reaction of liquid substances and has low sensitivity.
[0005] [Technical solution]
[0006] In order to solve the above problems, the present invention provides a polyaniline / phytic acid electrode covered with a hydrogel, a preparation method thereof, and an application in a pH sensor. The sensor provided by the present invention has a high sensitivity to pH, and the pH value of the substance to be tested is obtained by the voltage between the polyaniline / phytic acid electrode and the reference electrode. The present invention uses polyvinyl alcohol / sodium alginate hydrogel to cover the electrode surface, breaking through the limitation that traditional electrodes can only detect liquids, and has an electrochemical signal reflection of the pH change of volatile gases.
[0007] The present invention provides a method for preparing a polyaniline / phytic acid electrode covered with a hydrogel, the preparation method comprising the following steps:
[0008] (1) placing a PET (polyethylene terephthalate) substrate in a screen printer, printing a carbon substrate, and then printing an Ag / AgCl reference electrode using the screen printer after the carbon substrate is dried, and placing the printed electrode in a phytic acid, aniline, and sulfuric acid solution for polymerization to obtain a polyaniline / phytic acid electrode; the polymerization method is a constant potential polymerization method, the polymerization voltage is 0.8-1V, the polymerization time is 120-160s, and during the polymerization, an Ag / AgCl electrode is used as a reference electrode and a platinum column electrode is used as a counter electrode;
[0009] (2) adding polyvinyl alcohol (PVA) and sodium alginate (SA) into a mixed solution of glycerol (Gly) / water, and performing freeze-thaw gel preparation after complete dissolution;
[0010] (3) Covering the hydrogel obtained in step (2) on the polyaniline / phytic acid electrode to obtain a polyaniline / phytic acid electrode covered with the hydrogel.
[0011] In one embodiment of the present invention, in step (1), the carbon substrate is a conductive carbon paste.
[0012] In one embodiment of the present invention, in step (1), the polymerization voltage is 1 V and the polymerization time is 140 s.
[0013] In one embodiment of the present invention, in step (1), the solution for polymerization is composed of phytic acid, aniline and sulfuric acid solution, wherein the concentration of phytic acid in the solution is 0.01-0.1M, the concentration of aniline is 0.05-0.2M, and the concentration of sulfuric acid is 0.5-2M.
[0014] In one embodiment of the present invention, in step (2), the mass ratio of polyvinyl alcohol to sodium alginate is 10:1-2; the mass volume ratio of polyvinyl alcohol to the mixed solution of glycerol / water is 1:25-35, g / mL.
[0015] In one embodiment of the present invention, in step (2), the mass ratio of glycerol to water is 1:1.
[0016] In one embodiment of the present invention, in step (2), the mixed solution of PVA / SA / Gly is stirred in a 95°C water bath for 2 hours until the PVA is completely dissolved, and the completely dissolved solution without bubbles is poured into a mold, placed in a -20°C environment and frozen for 3 hours, then taken out, and placed at room temperature for 6 hours to form a gel for use.
[0017] The invention provides a polyaniline / phytic acid electrode covered with a hydrogel prepared by the method described above.
[0018] The present invention provides a pH sensor, which comprises the polyaniline / phytic acid electrode covered with hydrogel.
[0019] The present invention provides application of the above-mentioned pH sensor in detecting pH of food.
[0020] The present invention provides the use of the above-mentioned pH sensor in detecting the freshness of meat food.
[0021] The beneficial technical effects of the present invention are:
[0022] (1) The present invention adds phytic acid during polymerization. The addition of phytic acid can form a conductive polymer composite material with polyaniline. The three-dimensional porous matrix structure provides a larger contact area and a wider charge transfer path for hydrogen ions in the solution, which helps to improve the charge transfer efficiency of the electrode, thereby enhancing the conductivity of the electrode, thereby improving the sensitivity to pH. Moreover, when the polymerization conditions are 1V and 140s, the sensitivity is as high as 77.2mV / pH;
[0023] (2) The water retention of the hydrogel refers to the ability of the hydrogel to effectively keep the absorbed water from volatilizing or losing. In the present invention, the hydrogel is prepared and covered on the surface of the electrode. The hydrogel has good water retention and can absorb volatile substances released by corrupted fish meat. At the same time, good water retention can also prevent the hydrogel from drying out within a certain period of time, so that the electrode system operates well. The PVA / SA / Gly hydrogel of the present invention has good water retention and can achieve non-destructive monitoring of volatile substances released by meat when detecting the freshness of meat food.
[0024] (3) The electrode performance test experiment proved that the pH sensor has excellent sensitivity to pH and is selective for volatile amines in gaseous form; the porous structure within the hydrogel was observed by cryo-scanning electron microscopy; the freshness of fish meat was monitored non-contact and non-destructively using a pH sensor covered with hydrogel. The obtained electrical signal can be matched with the TVB-N content measured by the microdiffusion method, thereby achieving the effect of monitoring fish meat spoilage. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The scanning electron microscope images of the working electrode surfaces obtained in Comparative Example 1 and Example 1 are shown.
[0026] Figure 2 The Fourier transform infrared spectra of the working electrodes prepared in Comparative Example 1 and Example 1 are shown.
[0027] Figure 3 The X-ray photoelectron spectra of the working electrodes prepared in Comparative Example 1 and Example 1 are shown.
[0028] Figure 4 This is a cryo-scanning electron microscopy image of the hydrogel prepared in Example 1.
[0029] Figure 5This is the Fourier infrared spectrum of the hydrogel prepared in Example 1.
[0030] Figure 6 These are photos of the hydrogel prepared in Example 1 taken within 14 days.
[0031] Figure 7 The figure is a comparison chart of pH sensitivity of the electrodes prepared in Examples 1-4.
[0032] Figure 8 The electrode performance diagram of the pH sensor prepared in Comparative Example 1 and Example 1.
[0033] Fig. 9 The electrode performance diagram of the pH sensor prepared in Example 1 and Comparative Example 2.
[0034] Fig.10 The response curve of the pH sensor prepared in Example 1 to trimethylamine.
[0035] Fig.11 This is a graph showing the selectivity of the pH sensor prepared in Example 1 to different volatile solvents.
[0036] Fig.12 This is a graph showing the correspondence between the electrical signal of the pH sensor prepared in Example 1 for monitoring the freshness of fish meat and the TVB-N content. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0038] The polyvinyl alcohol used in the following is 1799 type polyvinyl alcohol, purchased from McLean.
[0039] Example 1
[0040] A method for preparing a polyaniline / phytic acid electrode covered with a hydrogel, the preparation method comprising the following steps:
[0041] (1) placing a PET substrate in a screen printer, printing a commercial conductive carbon paste as a carbon substrate, and then printing an Ag / AgCl reference electrode using the screen printer after the carbon substrate is dried;
[0042] (2) placing the printed electrode sheet into a 0.02 M phytic acid, 0.1 M aniline, and 1 M sulfuric acid solution to polymerize aniline / phytic acid to obtain a polyaniline / phytic acid electrode;
[0043] The electrochemical workstation was used to select the constant potential polymerization method, the polymerization voltage was 1 V, the polymerization time was 140 s, the reference electrode used in the polymerization was a commercial Ag / AgCl electrode, and the counter electrode was a commercial platinum column electrode;
[0044] (3) Add 1 g PVA and 0.1 g SA to a 30 mL glycerol / water (mass ratio 1:1) mixed solution, place the solution in a 95 °C water bath, heat and stir for 2 h until the PVA is completely dissolved, take it out and pour it into a mold and freeze it at -20 °C for 3 h, then thaw it at room temperature for 6 h before use;
[0045] (4) Covering the obtained hydrogel on the polyaniline / phytic acid electrode to obtain a polyaniline / phytic acid electrode covered with the hydrogel.
[0046] Comparative Example 1
[0047] A method for preparing a polyaniline electrode covered with a hydrogel, the preparation method comprising the following steps:
[0048] (1) placing a PET substrate in a screen printer, printing a commercial conductive carbon paste as a carbon substrate, and then printing an Ag / AgCl reference electrode using the screen printer after the carbon substrate is dried;
[0049] (2) placing the printed electrode sheet into a 0.1 M aniline and 0.2 M sulfuric acid solution to polymerize aniline;
[0050] The electrochemical workstation was used to select the constant potential polymerization method, the polymerization voltage was 1 V, the polymerization time was 140 s, the reference electrode used in the polymerization was a commercial Ag / AgCl electrode, and the counter electrode was a commercial platinum column electrode;
[0051] (3) Add 1 g PVA and 0.1 g SA to a 30 mL glycerol / water (mass ratio 1:1) mixed solution, place the solution in a 95 °C water bath, heat and stir for 2 h until the PVA is completely dissolved, take it out and pour it into a mold and freeze it at -20 °C for 3 h, then thaw it at room temperature for 6 h before use;
[0052] (4) Covering the obtained hydrogel on the polyaniline electrode to obtain a polyaniline electrode covered with the hydrogel.
[0053] Comparative Example 2
[0054] A method for preparing a polyaniline / phytic acid electrode covered with a hydrogel, the preparation method comprising the following steps:
[0055] (1) placing a PET substrate in a screen printer, printing a commercial conductive carbon paste as a carbon substrate, and then printing an Ag / AgCl reference electrode using the screen printer after the carbon substrate is dried;
[0056] (2) placing the printed electrode sheet into a 0.02 M phytic acid, 0.1 M aniline, and 1 M sulfuric acid solution for aniline / phytic acid polymerization;
[0057] The IT polymerization was selected using an electrochemical workstation, the polymerization voltage was 1 V, the polymerization time was 140 s, the reference electrode used in the polymerization was a commercial Ag / AgCl electrode, and the counter electrode was a commercial platinum column electrode;
[0058] (3) Add 1 g PVA and 0.1 g SA to a 30 mL glycerol / water (mass ratio 1:1) mixed solution, place the solution in a 95 °C water bath, heat and stir for 2 h until the PVA is completely dissolved, take it out and pour it into a mold and freeze it at -20 °C for 3 h, then thaw it at room temperature for 6 h before use;
[0059] (4) Covering the obtained hydrogel on the polyaniline / phytic acid electrode to obtain a polyaniline / phytic acid electrode covered with the hydrogel.
[0060] Comparative Example 3
[0061] A method for preparing a polyaniline / phytic acid electrode covered with a hydrogel, the preparation method comprising the following steps:
[0062] (1) placing a PET substrate in a screen printer, printing a commercial conductive carbon paste as a carbon substrate, and then printing an Ag / AgCl reference electrode using the screen printer after the carbon substrate is dried;
[0063] (2) placing the printed electrode sheet into a 0.02 M phytic acid, 0.1 M aniline, and 1 M sulfuric acid solution for aniline / phytic acid polymerization;
[0064] The electrochemical workstation was used to select the constant potential polymerization method, the polymerization voltage was 1 V, the polymerization time was 140 s, the reference electrode used in the polymerization was a commercial Ag / AgCl electrode, and the counter electrode was a commercial platinum column electrode;
[0065] (3) Add 80 mg of agarose and 116.8 mg of sodium chloride to 4 mL of water, stir on a magnetic stirrer at 520 rpm and 100 °C until the solution is clear and transparent, add the solution dropwise onto the electrode until the electrode surface is covered, and perform the test experiment after the solution has gelled.
[0066] Example 2
[0067] A method for preparing a polyaniline / phytic acid electrode covered with a hydrogel, the preparation method comprising the following steps:
[0068] (1) placing a PET substrate in a screen printer, printing a commercial conductive carbon paste as a carbon substrate, and then printing an Ag / AgCl reference electrode using the screen printer after the carbon substrate is dried;
[0069] (2) placing the printed electrode sheet into a 0.02 M phytic acid, 0.1 M aniline, and 1 M sulfuric acid solution to polymerize aniline / phytic acid to obtain a polyaniline / phytic acid electrode;
[0070] The electrochemical workstation was used to select the constant potential polymerization method, the polymerization voltage was 0.8 V, the polymerization time was 140 s, the reference electrode used in the polymerization was a commercial Ag / AgCl electrode, and the counter electrode was a commercial platinum column electrode;
[0071] (3) Add 1 g PVA and 0.1 g SA to a 30 mL glycerol / water (mass ratio 1:1) mixed solution, place the solution in a 95 °C water bath, heat and stir for 2 h until the PVA is completely dissolved; pour it into a mold and freeze it at -20 °C for 3 h, then thaw it at room temperature for 6 h before use;
[0072] (4) Covering the polyaniline / phytic acid electrode with the hydrogel to obtain a polyaniline / phytic acid electrode covered with the hydrogel.
[0073] Example 3
[0074] A method for preparing a polyaniline / phytic acid electrode covered with a hydrogel, the preparation method comprising the following steps:
[0075] (1) placing a PET substrate in a screen printer, printing a commercial conductive carbon paste as a carbon substrate, and then printing an Ag / AgCl reference electrode using the screen printer after the carbon substrate is dried;
[0076] (2) placing the printed electrode sheet into a 0.02 M phytic acid, 0.1 M aniline, and 1 M sulfuric acid solution to polymerize aniline / phytic acid to obtain a polyaniline / phytic acid electrode;
[0077] The electrochemical workstation was used to select the constant potential polymerization method, the polymerization voltage was 1 V, the polymerization time was 120 s, the reference electrode used in the polymerization was a commercial Ag / AgCl electrode, and the counter electrode was a commercial platinum column electrode;
[0078] (3) Add 1 g PVA and 0.1 g SA to a 30 mL glycerol / water (mass ratio 1:1) mixed solution, place the solution in a 95 °C water bath, heat and stir for 2 h until the PVA is completely dissolved, take it out and pour it into a mold and freeze it at -20 °C for 3 h, then thaw it at room temperature for 6 h before use;
[0079] (4) Covering the obtained hydrogel on the polyaniline / phytic acid electrode to obtain a polyaniline / phytic acid electrode covered with the hydrogel.
[0080] Example 4
[0081] A method for preparing a polyaniline / phytic acid electrode covered with a hydrogel, the preparation method comprising the following steps:
[0082] (1) Place the PET substrate in a screen printer, print commercial conductive carbon paste as a carbon substrate, wait for the carbon substrate to dry, and then use the screen printer to print the Ag / AgCl reference electrode.
[0083] (2) placing the printed electrode sheet into a 0.02 M phytic acid, 0.1 M aniline, and 1 M sulfuric acid solution to polymerize aniline / phytic acid to obtain a polyaniline / phytic acid electrode;
[0084] The electrochemical workstation was used to select the constant potential polymerization method, the polymerization voltage was 1 V, the polymerization time was 160 s, the reference electrode used in the polymerization was a commercial Ag / AgCl electrode, and the counter electrode was a commercial platinum column electrode;
[0085] (3) Add 1 g PVA and 0.1 g SA to a 30 mL glycerol / water (mass ratio 1:1) mixed solution, place the solution in a 95 °C water bath, heat and stir for 2 h until the PVA is completely dissolved, take it out and pour it into a mold and freeze it at -20 °C for 3 h, then thaw it at room temperature for 6 h before use;
[0086] (4) Covering the obtained hydrogel on the polyaniline / phytic acid electrode to obtain the polyaniline / phytic acid electrode covered with the hydrogel.
[0087] Test example:
[0088] 1. Scanning electron microscope: Use the X-Max50 energy dispersive spectrometer and backscattered electron diffraction analyzer produced by Oxford Instruments, UK. The specific operation is as follows: cut off the unpolymerized carbon substrate, the polymerized polyaniline and the working electrode of polyaniline / phytic acid, paste them on the test sample table, spray gold and then test to obtain the SEM scanning image.
[0089] Figure 1 The following are scanning electron microscope images of the working electrode surfaces obtained in Comparative Example 1 and Example 1. (a) (b) are unpolymerized carbon substrates; (c) (d) are polymerized polyaniline; (e) (f) are polymerized polyaniline / phytic acid. It can be seen from the figure that the polyaniline in Comparative Example 1 and the polyaniline / phytic acid in Example 1 are successfully polymerized on the surface of the carbon substrate. In addition, the polyaniline / phytic acid presents a more clustered morphology, which is conducive to the transmission of electrons.
[0090] 2. Infrared spectroscopy: A Fourier transform infrared spectrometer produced by Platinum Elmer Co., Ltd. was used, and the potassium bromide tablet method was adopted. The specific operation was as follows: spectrally pure potassium bromide powder and different working electrode powders were weighed in a ratio of 150:1, respectively, and placed in a mortar and ground until the powder size was less than 2.5μm. After grinding, the sample was taken out and placed in a tablet press to make a transparent or translucent disc of uniform thickness. The sample was taken out and tested.
[0091] Figure 2The Fourier transform infrared spectra of the working electrodes prepared in Comparative Example 1 and Example 1 are shown in Table 1. The FT-IR spectra show that the -1 The peak at 1300cm is the -C=N stretching vibration peak of the quinone unit doped in polyaniline. -1 The peak at 3446cm is the CN stretching vibration peak of the benzene ring unit in polyaniline. -1 The peaks at are the NH stretching of polyaniline or the -OH group of phytic acid. These peaks are different from the infrared vibration peaks of the carbon substrate, which proves the successful polymerization of polyaniline and polyaniline / phytic acid on the carbon substrate.
[0092] 3. X-ray photoelectron spectroscopy: XPS test was performed using an X-ray photoelectron spectrometer (ThermoFischer, ESCALAB250Xi, USA). The specific operation was as follows: the unpolymerized carbon substrate, the polymerized polyaniline and the working electrode of polyaniline / phytic acid were cut off, pasted on the test sample table, and tested after gold spraying to obtain the XPS spectrum.
[0093] Figure 3 The X-ray photoelectron spectra of the working electrodes prepared in Comparative Example 1 and Example 1 are shown in the figure. From the full spectrum in the figure, it can be seen that the electrode element compositions of different polymerized materials are different, which once again confirms the successful polymerization of polyaniline and polyaniline / phytic acid.
[0094] 4. Cryo-scanning electron microscopy: A cryo-scanning electron microscope of model SU8010 / PP3010T was used to characterize the internal microstructure of the hydrogel. 5-10 μL of the hydrogel prepared in Example 1 was placed on the sample stage and then frozen in liquid nitrogen. The frozen sample was fractured to observe its internal structure. After sublimation at -90°C for 30 min, the sample was gold plated for 60 s. Observation and imaging were performed under low temperature conditions.
[0095] Figure 4 This is a cryo-scanning electron micrograph of the hydrogel prepared in Example 1. The image shows the porous structure inside the hydrogel.
[0096] 5. Infrared spectroscopy (ATR): A Fourier transform infrared spectrometer produced by PerkinElmer Co., Ltd. was used to test the hydrogel sample prepared in Example 1 directly between the crystal and the ejector pin of the ATR accessory, and the hand twist was tightened to test the sample. The sample was then tested by a Fourier transform infrared spectrometer to obtain a spectrum of the sample.
[0097] Figure 5 This is the Fourier infrared spectrum of the hydrogel prepared in Example 1. The figure shows 3282 cm -1 The stretching vibration of OH group of PVA and the stretching vibration of -OH group of SA, 2937cm -1 CH stretching vibration at 1645cm-1 The peak at is attributed to the asymmetric stretching vibration of the carboxylate group.
[0098] 6. Investigation of the water retention of hydrogels: After placing the prepared hydrogels on the electrodes, take photos of the hydrogels every day during the experiment to observe the state of the hydrogels.
[0099] Figure 6 The following is a photo of the hydrogel prepared in Example 1 within 14 days. It can be seen that the hydrogel has basically not changed in appearance within 14 days, and has not lost water or wrinkled, which proves that it has excellent water retention. However, the agarose / sodium chloride hydrogel prepared in Comparative Example 3 will lose water and shrink after being placed for 48 hours, and its water retention is far inferior to that of the polyvinyl alcohol hydrogel of the present invention.
[0100] 7. Electrode performance test: The electrode performance was tested using the CHI760E electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. A Britton-Robinson buffer solution with a pH of 3-10 was prepared using 0.2M NaOH and mixed acid (H3BO3, HAC, and H3PO4 were all 0.04M), and the electrodes prepared in Examples 1-4 and Comparative Example 1 were used to perform pH sensitivity tests. The pH sensor prepared in Example 1 and 10g of skinless and boneless mackerel were placed in the same closed space, and stored at 4°C and 25°C, respectively, to detect electrical signals at different degrees of corruption (monitored once every 24h at 4°C for a total of 14 days, and monitored once every 6h at 25°C for a total of 60h).
[0101] Figure 7 The pH sensitivity comparison diagram of the electrode obtained in Examples 1-4. (a) is the polymerization condition of 1V, 140s, and the sensitivity is 77.2mV / pH; (b) is the polymerization condition of 0.8V, 140s, and the sensitivity is 67.4mV / pH; (c) is the polymerization condition of 1V, 120s, and the sensitivity is 61mV / pH; (d) is the polymerization condition of 1V, 160s, and the sensitivity is 65.64mV / pH. When the polymerization condition is 1V, 140s, the electrode has the highest sensitivity to pH, which is 77.2mV / pH. Therefore, the polymerization condition of polyaniline / phytic acid is determined to be 1V, 140s.
[0102] Figure 8 The electrode performance diagrams of the pH sensor prepared in Example 1 and Comparative Example 1 are shown. (a) The polymerized polyaniline / phytic acid is used as the working electrode, and the sensitivity to pH is 77.2 mV / pH; (b) The polymerized polyaniline is used as the working electrode, and the sensitivity to pH is 67.89 mV / pH, which confirms that the polymerized polyaniline / phytic acid is used as the working electrode to prepare the pH sensor.
[0103] Fig. 9The electrode performance diagrams of the pH sensor prepared in Example 1 and Comparative Example 2 are shown. Polyaniline / phytic acid is used as the working electrode. (a) The polymerization method is constant potential polymerization, and the electrode has a pH sensitivity of 77.2 mV / pH; (b) The polymerization method is IT method, and the electrode has a pH sensitivity of 71.5 mV / pH. It is confirmed that the pH sensor is prepared by constant potential polymerization of polyaniline / phytic acid.
[0104] 8. Electrode response experiment to trimethylamine: 35wt% trimethylamine solution was added into a 50mL centrifuge tube by adding different volumes of deionized water so that the vapor concentration of trimethylamine in the tube was 0, 0.017, 0.034, 0.05, 0.067, 0.073, 0.1, 0.34, 0.69, 1.06, 1.23, 1.56, 2.02, 2.45ppm, respectively. The sensor was covered at the tube mouth, and the response signal of the sensor to trimethylamine of different ppm was measured after the signal stabilized.
[0105] Fig.10 The response curve of the pH sensor to trimethylamine was obtained for Example 1. It can be seen from Figure (a) that the electrode is responsive to trimethylamine, and it can be seen from Figures (b) and (c) that the electrode has different response degrees to trimethylamine in different vapor concentration ranges. When the trimethylamine vapor concentration is 0-0.1ppm, the sensitivity of the electrode to trimethylamine is 4.793V / ppm; when the trimethylamine vapor concentration is 0.1-2.5ppm, the sensitivity of the electrode to trimethylamine is 0.013V / ppm.
[0106] 9. Electrode selectivity experiment: Place 20 mL of 1 M ammonia water, dimethylamine, trimethylamine, cadaverine, putrescine, n-hexane, methanol, acetaldehyde, dichloromethane, and chloroform in different 50 mL centrifuge tubes, cover the sensor at the tube mouth, measure the electrical signal data before and after the signal is stabilized at the tube mouth, and use ΔP / P0 as the comparison parameter.
[0107] Fig.11 The selectivity diagram of the pH sensor prepared in Example 1 to different volatile solvents is shown in FIG. From the figure, it can be seen that the polyaniline / phytic acid pH sensor only exhibits a large response to TVB-N, while the response to other volatile solvents is negligible.
[0108] 10. Determination of TVB-N content in fish meat: The TVB-N content of bluefin mullet with different degrees of corruption under different storage environments was determined by the microdiffusion method. The specific operation and calculation were based on the third method - microdiffusion method of the National Standard of the People's Republic of China GB 5009.228-2016 "National Food Safety Standard Determination of Volatile Basic Nitrogen in Food".
[0109] Three parallel experiments were conducted on each group of fish meat to obtain the TVB-N content of mackerel with different degrees of corruption and correspond to the electrical signals.
[0110] Fig.12 This is a graph showing the correspondence between the electrical signal of the pH sensor prepared in Example 1 for monitoring the freshness of fish meat and the TVB-N content. (a)(b) are the time-dependent changes of TVB-N content in fish stored at 25℃ and 4℃, respectively. It can be seen from the figure that under 25℃ environment, the TVB-N content of bluefin tuna increases with time, and slightly decreases in the later stage of corruption due to the weakening of microbial action. Under 4℃ environment, the TVB-N content of bluefin tuna continues to increase during the monitoring time; (c)(d) are the corresponding diagrams of TVB-N content and electrical signal. It can be seen that the TVB-N content of fish meat reaches the corruption standard of 30mg / 100g at 25℃ for 36h, and the corresponding electrical signal is 0.0285V at this time; at 4℃, the TVB-N content reaches the corruption standard of 30mg / 100g after 11 days, and the corresponding electrical signal is 0.1869V at this time. Therefore, when monitoring the corruption degree of fish meat, when the ambient temperature is 25℃ and the electrical signal of the pH sensor reaches 0.0285V or below, the fish meat has deteriorated; when the ambient temperature is 4℃ and the electrical signal of the pH sensor reaches 0.1869V or below, the fish meat has deteriorated.
[0111] In summary, the method of the present invention can prepare a polyaniline / phytic acid electrochemical pH sensor covered with polyvinyl alcohol / sodium alginate hydrogel, and the pH sensor has high sensitivity to pH. The technology can be used to monitor the degree of spoilage of fish meat, and has good market prospects.
[0112] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a polyaniline / phytic acid electrode covered with a hydrogel, characterized in that: The steps include: (1) placing a PET substrate in a screen printer, printing a carbon substrate, and printing an Ag / AgCl reference electrode after the carbon substrate is dried, and placing the printed electrode in a phytic acid, aniline, and sulfuric acid solution for polymerization to obtain a polyaniline / phytic acid electrode; (2) adding polyvinyl alcohol and sodium alginate into a mixed solution of glycerol / water, and freezing and thawing the mixture after the mixture is completely dissolved to obtain a hydrogel; (3) Covering the hydrogel obtained in step (2) on the surface of the polyaniline / phytic acid electrode to obtain a polyaniline / phytic acid electrode covered with the hydrogel.
2. The method for preparing a polyaniline / phytic acid electrode covered with a hydrogel according to claim 1, characterized in that: In step (1), the polymerization method is constant potential polymerization, the polymerization voltage is 0.8 to 1 V, and the polymerization time is 120 to 160 s.
3. The method for preparing a polyaniline / phytic acid electrode covered with a hydrogel according to claim 1, characterized in that: In step (1), the polymerization voltage is 1 V and the polymerization time is 140 s.
4. The method for preparing a polyaniline / phytic acid electrode covered with a hydrogel according to claim 1, characterized in that: In step (1), the carbon substrate is a conductive carbon paste.
5. The method for preparing a polyaniline / phytic acid electrode covered with a hydrogel according to claim 1, characterized in that: In step (1), the polymerization solution is composed of phytic acid, aniline and sulfuric acid solution, wherein the concentration of phytic acid in the solution is 0.01-0.1M, the concentration of aniline is 0.05-0.2M, and the concentration of sulfuric acid is 0.5-2M.
6. The method for preparing a polyaniline / phytic acid electrode covered with a hydrogel according to claim 1, characterized in that: In step (2), the mass ratio of polyvinyl alcohol to sodium alginate is 10:1-2; the mass volume ratio of polyvinyl alcohol to the mixed solution of glycerol / water is 1:25-35, g / mL; and the mass ratio of glycerol to water is 1:
1.
7. A polyaniline / phytic acid electrode covered with hydrogel prepared by the method of any one of claims 1 to 6.
8. A pH sensor comprising the polyaniline / phytic acid electrode covered with hydrogel according to claim 7.
9. Use of the pH sensor according to claim 8 in detecting the pH of food.
10. Use of the pH sensor according to claim 8 in detecting the freshness of meat products.